ANALYSIS OF FACTORS INFLUENCING THE ACCURRENCE OF DRUG STAGNANT AND STOCKOUTS AT THE MAUK COMMUNITY HEALTH CENTER, TANGERANG REGENCY - Jaka Supriyanta; Endang Sunariyanti; Lukman Hadi Permana (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2026)
Drug logistics is a process intended to achieve a specific goal that is carried out effectively and efficiently in the management of drugs to achieve predetermined objectives. The purpose of this study was to analyze drug management at the Mauk Community Health Center based on the guidelines of Ministry of Health Regulation No. 74 of 2016 and to analyze the factors that influence drug stagnation and stockouts at the Mauk Community Health Center. This study was a non-experimental, descriptive study using a cross-sectional observational method. The results of this study show that drug management at the Mauk Community Health Center UPTD is in accordance with the requirements of the 2016 Minister of Health Regulation No. 74 concerning pharmaceutical service standards at community health centers. However, there are still several obstacles in its implementation. One of the main obstacles is the length of time required for the procurement of drugs and disposable medical supplies. The conclusion of this study shows that stagnation and stockouts at the Mauk Community Health Center UPTD are caused by poor implementation of drug requests, as evidenced by only 22% of drug requests matching drug receipts and 78% of drug receipts not matching drug requests, as well as drug shortages or limitations from the Health Office, resulting in a mismatch between drug requests and drug receipts.